IMPLEMENTASI MODEL SUPERVISI BERBASIS KEIKHLASAN DALAM PENINGKATAN KINERJA GURU PAI DI SMP NEGERI KABUPATEN NAGAN RAYA - Herman, Herman; Idris, Jamaluddin (At-Tafkir, 2019)
The sincerity-based supervision model is one of the supervision models in promoting the values of sincerity as the first principle in the workplace, building identity in performing and taking actions, and becoming moral force for PAI supervisors when performing the main tasks and functions. However, the problem that most likely to arise in supervising tasks is the lack of sincerity of PAI supervisor when guiding, developing, and improving the performance of PAI teachers. This study uses a "descriptive" method, by discussing qualitative and inductive thought patterns of events, phenomena or natural phenomena encountered in the field. Data collection instruments were carried out through observation, interviews, and documentation studies. Furthermore, data analysis techniques will be based on the opinion of Miles and Huberman employing data reduction, data presentation, and concluding. Whereas checking the validity of the data is done through source triangulation, method triangulation, and theory triangulation. The results showed that the PAI supervisor had applied the value of sincerity when performing supervisory task for the PAI teacher through a model that was afraid of praise and fame that potentially  cause slander, regarding himself as inferior in the eyes of Him, performing acts of charity quietly and model of non-profit-seeking at work, and type of person who respect at others who surpass themselves. While due to the failure to uphold the values of sincerity at work, the sincerity-based supervision model performed by PAI supervisors, in terms of the effectiveness, has not shown optimal  results in improving the performance of PAI teachers.